The governance of infrastructure - Wegrich, Kai; Kostka, Genia; Hammerschmid, Gerhard (Oxford University Press, 2017)
Infrastructure only tends to be noticed when it is absent, declining, or decrepit, or when enormous cost overruns, time delays, or citizen protests make the headlines. If infrastructure is indeed a fundamental driver of economic growth and social development, why is it so difficult to get right? In addressing this perennial question, this volume-the fourth edition in an annual series tackling different aspects of governance around the world-makes the case for a governance perspective on infrastructure. This implies moving beyond rational economic analysis of what should be done towards an analysis of the political, institutional, and societal mechanisms that shape decision-making about infrastructure investment, planning, and implementation. Engaging with theories from sociology, political science, and public administration, and drawing on empirical analyses bridging OECD and non-OECD countries, the contributions to this volume dissect the logics of infrastructure governance in a novel way, providing timely analyses that will enrich both scholarly and policy debates about how to get infrastructure governance right